Windblown sand action on civil structures: Definition and probabilistic modelling. (1st January 2019) - Raffaele, Lorenzo; Bruno, Luca
Highlights: We reviewed the state of art of windblown sand effects on civil structures. Windblown sand is defined as an environmental variable action. A probabilistic modelling framework for windblown sand action is proposed. A desert railway protected by two alternative design solutions is tested. Abstract: The accurate prediction of windblown sand effects on structures and infrastructures is fundamental for their design and performance assessment in desert and coastal regions. Windblown sand occurs in the form of moving sand dunes, sand drift, sand erosion, accumulation, and avalanching around built structures. Windblown sand is here defined as an environmental variable action, analogously to wind or snow actions. We categorize its effects into Sand Ultimate Limit States and Sand Serviceability Limit States. We propose a framework to assess windblown sand action by means of a probabilistic method because of the inborn variability of the phenomenon. The proposed method is useful for the design of both structures and infrastructures and of sand mitigation measures. It allows to evaluate characteristic values of the sand action and assess related characteristic times of failures. In order to prove its technical feasibility, the proposed framework is then applied to a desert railway because of the particular sensitivity of such kinds of infrastructures to windblown sand action.